Notoraja sapphira sp. nov. (Rajoidei: Arhynchobatidae), a new deepwater skate from the slopes of the Norfolk Ridge (South-West Pacific) - Séret, Bernard; Last, Peter R. (Zootaxa, 2009)
A new arhynchobatid skate of the genus Notoraja is described from five specimens collected on the slopes of the Norfolk Ridge between 1195 and 1313 m depth. The new species is distinct from its sibling species from southern Australian waters, the Blue Skate (N. azurea), by its smaller size, several morphometric and meristic characters, thorn pattern and dorsal and ventral coloration.